RETRACTED: The Excellence of Pharmacy Practice - AK Mohiuddin (University of Minnesota Libraries Publishing, 2020)
This article has been retracted: please see INNOVATIONS in pharmacy retraction policy (https://pubs.lib.umn.edu/index.php/innovations/policies). This article has been retracted by the Editor and Publisher due to the inappropriate use of previously published work. Over the past 50 years, the role of pharmacists has evolved along with the health care needs of our population. In addition to dispensing medications and ensuring patient safety, today's pharmacists are taking a larger role as medical counselors, educators and advocates. They are integral part of the health care team, and are among the most trusted and accessible health care professionals. This accessibility allows them to perform more patient care activities, including counseling, medication management, and preventive care screenings. Beyond the care provided to individual patients, pharmacists have expanded their reach to influence the public health of communities. A pharmacist is uniquely positioned to provide disease state management through appropriate medication therapy management that has been demonstrated to improve patient outcomes and decrease overall health care costs. This role is more important than ever as the environment is demanding new practice and payment models that are required to further optimize care and outcomes while addressing the unsustainable increases in health care costs.   Article Type: Review